Optimization of Official Correspondence Management with Google Sheets - Rifki Ade Ananda; Moses Adeolu Agoi; Muhammad Yasin Simargolang (Ali Institute of Reseach and Publication, 2025)
Administrative management of letters in higher education environments still often faces various obstacles, especially if they are still using manual methods. At the Faculty of Tarbiyah and Teacher Training UINSU, the old system often causes delays in processing, errors in letter numbering, and difficulties when searching for archives. This study aims to see how the implementation of Google Sheets can help optimize digital letter management. The method used is descriptive qualitative, with data collected through direct observation and interviews with four administrative staff from three different divisions. The analysis was carried out using a thematic coding approach and inductive content. The results of the study showed a significant increase: the time for recording letters was reduced by 60%, searching for archives became 80% faster, and archiving time was also reduced by 80%. Numbering accuracy increased thanks to the automation feature, while transparency between units improved because all data could be accessed together in real time. In addition, the use of Google Sheets reduces operational costs because it does not require additional devices or software. From these findings, it can be concluded that Google Sheets is a simple but effective digital tool to help the administration process become more efficient, accurate, and transparent. This model also has the potential to be applied to other administrative units that are looking for practical solutions in the digitalization process.